The Influence of the Time Token Learning Model on Students' Speaking Skills in Indonesian Language Lessons - Sri Antoni; Eko Muda Setiawan (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research is motivated by the low speaking skills of students, this is indicated by the presence of some students still using non-standard, convoluted, and halting language so that the content of the conversation becomes unclear. One of the causes of low student skills is monotonous learning that makes students unable to express their opinions with the right sentence structure, appropriate word choices and appropriate expressions/mimics when speaking. The purpose of this study was to determine the effect of the time token learning model on students' speaking skills in the Indonesian language subject of class IV MIN 3 Tanah Datar. This type of research is experimental research using a pre-experimental design with a one group pretest-protest design type. The population and sample in this study amounted to 23 people or all class IV students. The sample collection technique in this study is the Purpose Sampling technique. The instruments used to collect speaking skills data are tests and observation sheets of students' speaking skills which will be given at the beginning of learning and at the end of learning. The data analysis technique used by the researcher is a prerequisite test and a hypothesis test using a paired sample t-test. The results of the study showed that the average pretest obtained was 40.2. Meanwhile, the average posttest was 75.3. This is evidenced by the results of the t-test sig value (2-tailed) 0.000 <0.05. So it can be concluded that Ho is rejected and Ha is accepted with a significant level <a (0.000 <0.05). This means that there is an influence of the time token learning model on students' speaking skills in the Indonesian language subject of class IV MIN 3 Tanah Datar.